Structural glass envelopes – Implementation of environmental studies into viscoelastic analysis - Lisa Rammig; Peter Lenk; Vladimir Marinov (Journal of Facade Design and Engineering, 2015)
The focus of this paper is to promote close collaborations of facade and structural engineers through integration of design services in order to deliver more optimal glass envelopes. To achieve the best performance, this process involves a careful selection of glass and coatings, radiation analysis to maximise daylight while controlling solar gain, and preventing overheating of spaces as well as careful detailing. Site-specific environmental data are used to accurately determine the performance requirements of the glass. Once the environmental impact is assessed the temperature in the interlayer is calculated over any chosen time domain. As part of the proposed process, a technique for determining the time-dependent structural behaviour of SGP laminated glass under varying temperature loads is also considered. In conclusion the authors examine the possibility of integration of both environmental and structural design approaches through the use of parametric software.